1995
DOI: 10.1002/psc.310010307
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of the first all‐aza analogue of a biologically active peptide

Abstract: The synthesis of the first all-aza-amino acid analogue (2) of a peptidic renin inhibitor is described. The X-ray structural analysis and molecular modelling investigations of this novel compound reveal interesting conformational features which have a significant impact on its biological activity. In addition, insight into conformational features of azapeptides in general in comparison with the corresponding purely peptidic compounds is given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 10 publications
(4 reference statements)
2
32
0
Order By: Relevance
“…There are numerous literature examples of the use of azapeptides as peptide mimetics, particularly as protease inhibitors and beta-turn inducing substitutions 235,236 but also as enzyme active sites titrants, 237±242 Leu-enkephalin, 243 eledoisin, 244 RGD mimetics, 245 and renin inhibitors. 246,247 Studies have demonstrated azapeptide resistance to amino-and carboxy-peptidases and they have also been used as prodrugs. 248 It has been recently shown that that the azapeptide conformational bias is neither disruptive to binding the MHC II protein nor to T-cell activation.…”
Section: D E S I G N O F P E P T I D E -M I M E T I C S T H a T Bmentioning
confidence: 99%
“…There are numerous literature examples of the use of azapeptides as peptide mimetics, particularly as protease inhibitors and beta-turn inducing substitutions 235,236 but also as enzyme active sites titrants, 237±242 Leu-enkephalin, 243 eledoisin, 244 RGD mimetics, 245 and renin inhibitors. 246,247 Studies have demonstrated azapeptide resistance to amino-and carboxy-peptidases and they have also been used as prodrugs. 248 It has been recently shown that that the azapeptide conformational bias is neither disruptive to binding the MHC II protein nor to T-cell activation.…”
Section: D E S I G N O F P E P T I D E -M I M E T I C S T H a T Bmentioning
confidence: 99%
“…Later they also investigated the influence of multiple aza-replacement in the same molecule on the biological activity and they synthesised an all-azaamino acid analogue of the peptide renin inhibitor. The rigidity caused by the aza moiety leads to poorer fitting into the binding site and therefore reduced activity [82].…”
Section: Protease Inhibitors and Active Site Titrantsmentioning
confidence: 99%
“…Moreover, after amidification of the carbazic acid chloride 10, the ester function of 11, 15 and 19 can be saponified into a carboxylic group (13,16) or converted into a carboxamide group by aminolysis (14a±c, 17a±c and 20), so giving access to the AzAsp or AzAsn residue. The carboxylic group in 16 also reacted with a secondary amine (dimethylamine) to give a N d ,N d -disubstituted AzAsn residue (18).…”
Section: Liquid-phase Aza-peptide Synthesismentioning
confidence: 99%
“…451, 1 rue Grandville, 54001 Nancy, France. 11,13]. However, coupling requires in both cases a high temperature and long reaction times, and often results in low yields with numerous side products such as phenolic derivatives, hydantoins [9,10] and oxadiazolones [4,12,14].…”
mentioning
confidence: 99%